2023
DOI: 10.18240/ijo.2023.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ocular trauma between normalized and the COVID-19 epidemic periods in China: a multi-center cross-sectional study

Abstract: AIM: To compare the feature of ocular trauma between normalized period and the COVID-19 epidemic period in China, and to provide a profile for eye injuries in special times in future. METHODS: This is a multi-center cross-sectional study with 30 participated hospitals involving the China Ocular Trauma Society members. All hospitalized cases who visited the Ophthalmology Department in participated hospitals with eye injuries during the normalized period (2019) and the COVID-19 epidemic period (2020) were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“… 7 Previous studies have indicated that an increase in both the age-standardised rates (ASR) of incidence and number of years lived with disability (YLDs) from eye injuries due to intraocular foreign bodies are going to present a global health challenge. 8 , 9 In addition to foreign body injuries, there are many causes of eye injuries, such as explosive eye injuries, 10 road traffic injuries, 11 mechanical or non-mechanical eye injuries (chemical/thermal/radiation), 12 and even self-inflicted injuries. 13 However, the incidence of and burden from eye injury have not been reported, and there has been no information regarding age-, sex-, spatial-, and temporal patterns of eye injury worldwide.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Previous studies have indicated that an increase in both the age-standardised rates (ASR) of incidence and number of years lived with disability (YLDs) from eye injuries due to intraocular foreign bodies are going to present a global health challenge. 8 , 9 In addition to foreign body injuries, there are many causes of eye injuries, such as explosive eye injuries, 10 road traffic injuries, 11 mechanical or non-mechanical eye injuries (chemical/thermal/radiation), 12 and even self-inflicted injuries. 13 However, the incidence of and burden from eye injury have not been reported, and there has been no information regarding age-, sex-, spatial-, and temporal patterns of eye injury worldwide.…”
Section: Introductionmentioning
confidence: 99%